Modern concepts of the equilibrium real exchange rate estimates - Brankica Pažun (Mенаџмент у хотелијерству и туризму, 2014)
Ambivalent attitudes of experts and different empirical results, often unsuccessful, as a result of the application of traditional concepts forming the exchange rate contributed to a new wave of research on the equilibrium real exchange rate, which basically see exchange rate fundamental variables as factors that determine its equilibrium or sustainable level. While the choice of fundamental variables, although in general defined, depends on the country which is the object of study, as well as the authors themselves and methodology. This paper aims to show one of many methods used to estimate the equilibrium real exchange rate, as well as the real exchange rate deviation from its estimated level - the concept of fundamental equilibrium exchange rate - FEER.